Studi Pengaruh Powder Factor Terhadap Fragmentasi Peledakan Dan Produktivitas Alat Gali Muat Di PT. Ansaf Inti Resources Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Fernando Lawangan; Agus Winarno; Revia Oktaviani (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2022)
One of the successes of a blasting is if the results of fragmentation are obtained with good size and relatively uniform so that the production target can be met. The size of the fragmentation was analyzed using Split Desktop 2.0 which resulted in a curve of the size of the fragmentation and the percentage of sieve pass (screening), at Pit 2 the optimal powder factor was between 0.20 kg/m³-0.26 kg/m³, while at Pit 7 it was between 0.22 kg/m³-0.24 kg/m³ which results in top size fragmentation in March 25.02 cm-43.2 cm, April April 35.37 cm-50.59 cm, May 19.79 cm-32.28 cm, June 26.45 cm-63.69 cm, which affect the digging time generated from the Komatsu PC 400 Excavator with an average top size fragmentation size of 38.33 cm with an average digging time of 7.95 seconds, while the Hyundai R 850 LC-9 Excavator with a fragmentation top size the average top size is 33.97 cm with an digging time of 8.44 seconds, with the average productivity of the Komatsu PC 400 Komatsu of 198.49 BCM/Hour from a plan productivity of 200 BCM/Hour while the Hyundai R 850 LC-9 average productivity a of 364.41 BCM/Hour from the plan productivity of 350 BCM/Hour